Ferric ammonium citrate (FAC)-induced inhibition of osteoblast proliferation/differentiation and its reversal by soybean-derived peptides (SDP). (October 2021) - Wang, Fang; Weng, Zebin; Song, Haizhao; Bao, Yifang; Sui, Huilin; Fang, Yong; Tang, Xiaozhi; Shen, Xinchun
Abstract: Ferric citrate has been used to treat hyperphosphatemia, a prevalent symptom in patients with chronic kidney disease while ferric ammonium citrate (FAC), a more dissolvable format, is widely used as food additive. However, excess iron is associated with osteoporosis. Dietary soybean products have been shown to prevent the progression of osteoporosis. In this study, a group of peptides, referred as P3, was identified from the enzymolysis of soybean protein isolates, and its biological functions were investigated. The results showed that MC3T3-E1 cell cycle progression from G0/G1 to S phase was accelerated by P3 treatment. MC3T3-E1 cell proliferation was enhanced by P3 via ERK1/2 activation. Importantly, P3 treatment abolished the antiproliferative effect of FAC on MC3T3-E1 cell. In addition, P3 treatment increased the expression of ALP, COL-1, OCN, consequently promoting the differentiation and mineralization of MC3T3-E1 cells via activation of p38 MAPK pathway. Consequently, P3 treatment was able to reverse the inhibitory effect of FAC on osteoblasts differentiation and mineralization. Our findings suggest P3, as a dietary supplement, has a potential therapeutic function to attenuate the adverse effects of FAC on bone metabolism and to prevent osteoporosis progression.